Noohumanism as a New Worldview Paradigm of the 21st century - Raushan Shindaulova (Философия и космология, 2022)
The article discloses the prerequisites of the Noohumanism, which incorporates the noosphericenvironmental as well as the humanistic components. Studied is the role of the principle of harmony as a basic cornerstone element of the Noohumanism. The metaprinciple, being projected through each level of the “human-society-nature” system, generates the axiological array of the noohumanism and plays the regulatory role in forming the noohumanistic senses and values. The aim hereof is to provide a rationale for the author’s development of the worldview potential of the noohumanism as the homonymous worldview concept based on the synthesis of the noosphericenvironmental and humanistic worldview matrices. The noohumanistic worldview focused on the harmonization of the socio-natural systems shall be formed applying adequate approach, in this particular case, the noohumanistic approach, which plays the methodological role within the scope of the handled problem. The noohumanistic approach, as elaborated by the author, is the complex research method that helps to argue and approves the conceptual bases lying under the formation of the noohumanistic worldview and to structurize the framework of the determinant noohumanistic categories and concepts. The noohumanistic approach incorporates: (a) the mixed-level analysis and the subset of approaches (axiological, interdisciplinary, regional, psycho-didactic, musicological et al.), exposing the philosophicalanthropological, culturological, psychological-pedagogical and other requisites that predetermine the sociocultural, worldview-wise and moral significance of the noohumanism; (b) the noohumanistic ideas tracing their origins back to the philosophic, naturalistic, interdisciplinary areas of knowledge. The noohumanistic approach reflects the relevancy of the introduced worldview system as a social demand of the present. The scientific finding that resulted from the noohumanistic approach is the developed theoreticalmethodological and methodical framework of the noohumanistic worldview within the scope of the philosophy of education to provide blueprint principles for the incipient noohumanistic pedagogy – one of the most prospective areas of contemporary education. The practical implication hereof is that the study materials may be put into scholarly circulation and used in developing the strategies of the educational modernization, the youth policy and within the teaching and learning activities.